Aggregative behavior of blackfin tuna (Thunnus atlanticus) following a fishing boat in the southwestern tropical Atlantic Ocean - Guelson Batista da Silva; Paulo Victor do Nascimento Araújo (Ocean and Coastal Research)
The blackfin tuna (Thunnus atlanticus) is a small epipelagic species restricted to the western and central Atlantic Ocean that has aggregative behavior, living in large schools usually associated with other tunas and commonly caught near moored Fish Aggregating Devices (FAD) or natural floating objects. This work offers the first report of a blackfin tuna school following a fishing boat serving as a drifting FAD in the southwestern tropical Atlantic Ocean, which occurred during the tagging campaign for the Atlantic Ocean Tropical Tuna Tagging Program (AOTTP) in May 2019. The blackfin tuna school followed the boat for approximately 190 nautical miles during almost 60 hours. The school remained close to surface when the boat was in motion but moved to deeper waters (60 m) in those few moments when the boat remained drifting. Along with the tagging activities, which occurred mainly in the morning, we caught 17 blackfin tunas with size ranging from 46 to 58 cm fork length (FL) (mean ± SD: 52.47 ± 3.35 cm FL) and weight ranged from 2.3 to 4.04 kg (3.2 ± 0.5 kg).